Implementasi Media Digital dan Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam - Agisni Bepi Rosadi; Alya Nur Fauziyah; Fatihul Noer Ihsan; Nabilla Nur Amalia (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The field of education, especially Islamic Religious Education (PAI), has seen substantial changes as a result of the advancement of digital technology and artificial intelligence (AI). The existence of digital media and AI offers numerous opportunities to improve the effectiveness, efficiency, and quality of education through interactive, flexible, and easily accessible learning resources. The purpose of this article is to analyze how artificial intelligence (AI) and digital media are used in Islamic Religious Education. This includes the idea of AI and digital media, AI-based learning materials, the use of AI in educational activities, ethical considerations of AI use, the effects and difficulties of integrating AI, and the Islamic viewpoint on technological advancement. This study employed a library research method by collecting data from relevant journals, books, and other scholarly sources. The findings indicate that the use of AI and digital media in PAI learning can enhance access to information, personalize learning experiences, improve evaluation effectiveness, and increase student engagement in the learning process. However, the implementation of AI also presents several challenges, such as limited digital literacy among teachers, inadequate facilities and infrastructure, ethical concerns, and the potential decline of direct educational interaction between teachers and students. Therefore, the utilization of AI in Islamic Religious Education should be carried out wisely while maintaining Islamic values, ethics, and the primary goal of Islamic education in shaping students’ character.